1998
DOI: 10.1017/s0033291798006795
|View full text |Cite
|
Sign up to set email alerts
|

Spouse similarity for lifetime psychiatric history in the general population

Abstract: The existence of associations between spouses for the presence of psychiatric disorders, either similar or different, has significant implications for both clinicians and researchers. Future research should aim at exploring the aetiological mechanisms of these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 39 publications
6
39
3
Order By: Relevance
“…Our findings for depression support the results of the meta-analysis of Mathews & Reus (2001), who found little, but significant, marital resemblance for affective disorders. The finding of marital resemblance for anxiety symptoms in this study confirms various earlier reports in both clinical and population-based studies (Tambs, 1991 ;Zimmermann-Tansella & Lattanzi, 1991 ;McLeod, 1995 ;Galbaud du Fort et al 1998 ;Maes et al 1998 ;Dubuis-Stadelmann et al 2001), reporting correlations between 0.1 and 0.3 using either diagnostic or dimensional ratings of anxiety. Two studies did not find marital resemblance for anxiety disorders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings for depression support the results of the meta-analysis of Mathews & Reus (2001), who found little, but significant, marital resemblance for affective disorders. The finding of marital resemblance for anxiety symptoms in this study confirms various earlier reports in both clinical and population-based studies (Tambs, 1991 ;Zimmermann-Tansella & Lattanzi, 1991 ;McLeod, 1995 ;Galbaud du Fort et al 1998 ;Maes et al 1998 ;Dubuis-Stadelmann et al 2001), reporting correlations between 0.1 and 0.3 using either diagnostic or dimensional ratings of anxiety. Two studies did not find marital resemblance for anxiety disorders.…”
Section: Discussionsupporting
confidence: 91%
“…Findings for depressive and anxiety disorders, however, are not unequivocal. For anxiety disorder, some studies found no evidence of increased risk of anxiety disorder in spouses of patients with an anxiety disorder (Eagles et al 1987 ;Low et al 2007), but several other studies found an increased risk (Tambs, 1991 ;Zimmermann-Tansella & Lattanzi, 1991 ;McLeod, 1995 ;Galbaud du Fort et al 1998 ;Dubuis-Stadelmann et al 2001), with spousal correlations varying between 0.1 and 0.3. Only one study mentioned data on marital resemblance for obsessive-compulsive disease (OCD).…”
Section: Introductionmentioning
confidence: 99%
“…This similarity has been found for affective disorders (Galbaud du Fort, Bland, Newman, & Boothroyd, 1998) and antisocial behavior (Krueger, Moffitt, Caspi, Bleske, & Silva, 1998). Yamaguchi and Kandel (1993) found significant concordance for drug use in couples both prior to and during their marriage.…”
supporting
confidence: 78%
“…Extant findings provide some suggestion that assortative mating may be more likely to occur for individuals with lifecourse persistent antisocial behavior than for those with adolescent-limited antisocial behavior (Sakai et al, 2004); that cross-disorder assortment may not be significant after controlling for within-disorder similarity (Galbaud du Fort, 1998;Sakai et al, 2004); and that there may be gender differences in these relationships (Galbaud du Fort, 1998;Sakai et al, 2004;Kandel, 1993, 1997), with women being more likely to have partners who match their involvement in problem behavior and more likely to be affected by their partner's problem behavior (Haynie et al, 2005;Moffitt et al, 2001; see continued discussion later in paper). However, these initial conclusions may be premature in that they are each based on only a handful of studies, with some discrepancy among studies.…”
Section: Summary Of Findings Regarding Partner Similarity In Problem mentioning
confidence: 92%